1994
DOI: 10.1128/mcb.14.2.982
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic expression cloning of a novel human tyrosine kinase.

Abstract: 496-8479. threonine residues when examined in bacterial expression systems or in vitro assays (3,5,22,26). This has led to the classification of a third group of enzymes referred to as dual-specificity protein kinases (19).In the present report, we describe the prokaryotic expression cloning and in vitro characterization of a novel protein kinase from a human embryonic lung fibroblast cDNA library by using an anti-pTyr monoclonal antibody. When expressed as a 0-galactosidase fusion protein, this molecule de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…1). However, previous biochemical studies with a human homologue of twinfilin suggested that it was a tyrosine kinase (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). However, previous biochemical studies with a human homologue of twinfilin suggested that it was a tyrosine kinase (4).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies with these human and mouse proteins did not reveal any actinrelated activities in these proteins but instead suggested that they would constitute a novel class of protein tyrosine kinases. Therefore, these proteins were named A6 tyrosine kinases (4,5).…”
mentioning
confidence: 99%
“…Phosphate groups can lead to poor cell penetration and predicted instability due to endogenous phosphatases. Because bacteria lack tyrosine kinase activity, the peptides on the phage are not expected to contain phosphorylated tyrosine residues (69). Additional evidence that the peptide phage are not phosphorylated is provided by the fact that the synthetic peptides were not phosphorylated and yet were able to effectively compete with the peptide displayed on the phage for binding to Grb7.…”
Section: Figmentioning
confidence: 99%
“…Subdomain VIII appears to play a major role in the recognition of peptide substrates, and contains several autophosphorylation sites, required for maximal kinase activity in many protein kinases. No clear ATP-binding site is identified as in the Bcr protein serine/threonine kinase (42) and in the human A6 tyrosine kinase (43). Clone 5 could represent a new example of these atypical kinases, and work is currently in progress to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%